2011
DOI: 10.1103/physrevb.83.180501
|View full text |Cite
|
Sign up to set email alerts
|

Nonmagnetic pair-breaking effect in La(Fe1xZnx)AsOet al.

Abstract: As and139 La NMR and nuclear quadrupole resonance (NQR) studies on Zn-substituted LaFeAsO0.85 have been performed to investigate the Zn-impurity effects microscopically. Although superconductivity in LaFeAsO0.85 disappears by 3% Zn substitution, we found that NMR/NQR spectra and NMR physical quantities in the normal state are hardly changed, indicating that the crystal structure and electronic states are not modified by Zn substitution. Our results suggest that the suppression of superconductivity by Zn substi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…1 Accordingly, the effects of transition metal ion substitution [2][3][4][5] or the introduction of deficiencies [6][7][8] on the superconducting ground state of iron-based superconductors have been intensively studied during the last years. The superconductors of the LnFe 1−x M x AsO 1−y F y (Ln1111) family, with Ln = La, Ce, Nd, Sm, ... and M = impurity elements doped on the Fe site, are one of the example systems used in such studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Accordingly, the effects of transition metal ion substitution [2][3][4][5] or the introduction of deficiencies [6][7][8] on the superconducting ground state of iron-based superconductors have been intensively studied during the last years. The superconductors of the LnFe 1−x M x AsO 1−y F y (Ln1111) family, with Ln = La, Ce, Nd, Sm, ... and M = impurity elements doped on the Fe site, are one of the example systems used in such studies.…”
Section: Introductionmentioning
confidence: 99%
“…The Ru substitution is also observed to induce static magnetism for x > 10%, 10,11 indicating the importance of the change of the electronic state caused by relatively high doping levels. There are also many reports on the effect of Zn doping in Fe-based superconductors 5,[12][13][14] and on the relevance of the observed electron localization taking place at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, isovalent substitution at the Fe site [10][11][12][13] has been used to study the effect of disorder on the superconductivity. Apart from the effect on the superconductivity, these studies were also motivated by the possiblity to answer the question of the symmetry of order parameter in the iron-based superconductors [14,15], either in the spin-fluctuation approach [16][17][18] with anion height as a key parameter [18], or the orbital fluctuations mediated superconductivity with iron-phonons [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) can probe nuclei coupled to the superconducting Fe 2 X 2 planes to yield information on the local magnetic structure. Kitagawa et al 16 studied the Zn-substituted LaFeAsO 0.85 polycrystal using 75 As and 139 La NMR and nuclear quadrupole resonance, and found that the suppression of superconductivity by Zn is not due to the change of the normal-state properties, but due to a strong non-magnetic pair-breaking effect on superconductivity. On a local-scale of suppression, the Zn ions can exclude the supercurrent of an unconventionally gapped superconductor within an area of , which results in a two-dimensional (2D) ‘Swiss cheese'-like supercurrent distribution; here ξ ab is the in-plane coherence length of the superconductor.…”
mentioning
confidence: 99%